Factors Related to Mother of Toddler to Come to Integrated Healthcare Center - Hilda Hidayat; Nurmaines Adhyka; Selly Wardianti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Integrated Healthcare Center (IHC) is basic health activities, mostly for toddler, organized by, from and for the community. The numbers of IHC who run their activity since 2019 are 283,370 but only 173,750 (61.32%) which do the services regularly every month. The problem is, there are only 38,68% parents that bring their children to visit IHC to maintains their health. The purpose of the study was to determine the factors related to parents, especially the mother, bringing their children to visit IHC in Tanjung Batang Kapas Village which is part of Pancung Soal Health Center area, in Pesisir Selatan Regency, West Sumatera, Indonesia. This is analytic research with cross sectional design, this research was carried out in January - July 2022. The population of this study was mothers who has baby under five, it is amounted in 114 people. Proportional random sampling technique was used to collect 89 samples. The data were analyzed by univariate and bivariate using Chi Square test. The results of this study found that there was a significant relationship between knowledge (p-value=0.044), attitude (p-value=0.000), education (p-value = 0.000), family support (p-value=0.015), motivation (p-value=0.000), the role of IHC cadres (p-value=0.000) with Toddler IHC Visits. In contrast, health workers roles (p-value=0.167) and parent occupation (p-value=0.326) did not have a connection of toddlers coming to IHC in Tanjung Batang Kapas Village in 2022. It is expected that health workers will be more active in carring toddler to IHC by doing something interesting while weighing toddlers, doing immunization, and improving nutrition status based on government programs, and cadres home visits to be encouraged by the head of public health center by giving more information about the benefits of IHC so that the families can support mothers to came posyabdu once a month. Keywords: IHC, Public Health Centre, Toddler, Visit